RUMAH PANJANG DAN PERUBAHAN FUNGSINYA KAJIAN SOSIAL PADA MASYARAKAT DAYAK DI KABUPATEN KUTAI BARAT - Hartatik Hartatik (Naditira Widya, 2009)
A long house is a traditional communal house, which is occupied by a number of Dayak families. Such house usually accomodates traditional ceremonies sush as marriage, mortuary and other traditional gatherings. Today, most of the long houses are abandoned and deteriorate, and what is left is mere symbol of old custom which is also gradually dimishing. This article discusses the archaeological and sociological perspective on factors causing of the degrading existence and function of long houses of the Dayak in Kutai Barat.